Occurrence of Microdictyon from the lower Cambrian Xinji Formation along the southern margin of the North China Platform - Pan, Bing （潘兵）; Topper, Timothy P.; Skovsted, Christian B.; Miao, Lanyun （苗兰云）; Li, Guoxiang （李国祥） (Journal of Paleontology, 2018)
Disarticulated net-like plates of the lobopod Microdictyon had a near cosmopolitan distribution from the early to middle Cambrian but are yet to be documented from the North China Platform. Here we report isolated plates of Microdictyon from the lower Cambrian Xinji Formation (Stage 4, Series 2) of the North China Platform, extending the paleogeographic distribution of Microdictyon in the early Cambrian. The plates of Microdictyon from the Xinji Formation are similar to those of other species established on the basis of isolated plates but do bear some new characters, such as mushroom-shaped nodes with a single inclined platform-like apex and an upper surface that displays radial lines. However, the plates documented here are left under open nomenclature due to inadequate knowledge of intraspecific and ontogenetic variation and low specimen numbers. Through comparison of the node shapes of the isolated plates of different Microdictyon species, we consider that low mushroom-shaped nodes could be a primitive and conservative character of Microdictyon while tall mushroom-shaped nodes may be a derived character. Subtle differences in shape and number of node apices may also represent intraspecific or ontogenetic variation.